Development of a Sensitive Quantum Dot-Linked Immunoassay for the Multiplex Detection of Biochemical Markers in a Microvolumeric Format - Kalvaityte U; Bagdonas E; Kirdaite G; Kausaite-Minkstimiene A; Uzieliene I; Ramanaviciene A; Popov A; Butkiene G; Karabanovas V; Denkovskij J; Mobasheri A; Bernotiene E (International Journal of Nanomedicine)
Ursule Kalvaityte,1 Edvardas Bagdonas,1 Gailute Kirdaite,2 Asta Kausaite-Minkstimiene,3,4 Ilona Uzieliene,1 Almira Ramanaviciene,3,4 Anton Popov,3,4 Greta Butkiene,1,5 Vitalijus Karabanovas,1,5 Jaroslav Denkovskij,1 Ali Mobasheri,1,6– 8 Eiva Bernotiene1,9 1Department of Regenerative Medicine, State Research Institute Centre for Innovative Medicine, Vilnius, LT-08406, Lithuania; 2Department of Personalised Medicine, State Research Institute Centre for Innovative Medicine, Vilnius, Lithuania; 3Department of Immunology and Bioelectrochemistry, State Research Institute Centre for Innovative Medicine, Vilnius, LT-08406, Lithuania; 4NanoTechnas - Center of Nanotechnology and Materials Science, Faculty of Chemistry and Geosciences, Vilnius University, Vilnius, LT-03225, Lithuania; 5Biomedical Physics Laboratory, National Cancer Institute, Baublio 3b, Vilnius, LT-08406, Lithuania; 6Research Unit of Health Sciences and Technology, Faculty of Medicine, University of Oulu, Oulu, 90014, Finland; 7World Health Organization Collaborating Center for Public Health Aspects of Musculoskeletal Health and Aging, Université de Liège, Liège, B-4000, Belgium; 8Department of Joint Surgery, First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 9Faculty of Fundamental Sciences, Vilnius Gediminas Technical University, Vilnius, LT-10223, LithuaniaCorrespondence: Eiva Bernotiene, Department of Regenerative Medicine, State Research Institute Centre for Innovative Medicine, Santariskiu G. 5, Vilnius, LT-08406, Lithuania, Tel +37068377130, Email eiva.bernotiene@imcentras.ltPurpose: For the diagnosis of various diseases, simultaneous sensitive detection of multiple biomarkers using low sample volumes is needed. The purpose of the present research was to develop sensitive multiplex detection model of QD-based ELISA (QLISA), through the spectroscopic QD-analyte complex measurements in microvolume liquid droplets on a glass microslide.Methods: QLISA was used for the detection of cartilage oligomeric matrix protein (COMP) and human growth hormone (hGH) as model analytes. The QLISA detection method included the formation of complexes consisting of analyte antigens, biotinylated antibodies and streptavidin-coated QDs. A specific immune-complex disassembling solution was used to dissociate analyte-antibody complexes from the bottom of the 96-well plate. After dissociation, the samples were diluted with PBS, and 2 μL transferred to a reusable glass slide for fluorescence (FL) scan.Results: The alkaline immune-complex disassembling solution that most efficiently amplified QDs FL within a prolonged 17 h time was selected. Comparison of median fluorescence intensity (MFI) of 50 nM COMP, 25 nM COMP, and 5 nM COMP detection using QD655 with the dilution of the detached samples with PBS and without dilution resulted in significant MFI differences in all cases. The FL signal readouts from QD655 in the microvolume format were from 10 to 40 times stronger than those measured directly from a 96-well plate QLISAs. In duplex analysis, two analytes COMP and hGH were measured using different QD605 and QD525 in the same well. In the respectful 96-well plate QLISA format, two different analyte concentrations can be hardly distinguishable, but the transfer to micro-volumetric detection on the glass slide highly increased the signal strength according to green and red FL intensity of QDs.Conclusion: Our method significantly enhances detection sensitivity, as compared to measured in parallel QLISAs in a 96 well plate format, enables multiplexing and may prove very valuable for samples of limited volumes.Keywords: quantum dots, biomarker, microvolume, FL spectroscopy, immunoassay, QLISA